Pengaruh Kondisi Kesehatan Lingkungan Terhadap Kepuasan dan Jumlah Kunjungan Pasien di Puskesmas Kota Pekanbaru - Sulistiawati, Mailinda; Zulkarnaini, Zulkarnaini; Zahtamal, Zahtamal (Dinamika Lingkungan Indonesia, 2018)
Given the importance of environmental health at puskesmas in the environmental health care system to create a healthy environment that can provide protection for patients and puskesmas. This study aims to analyze the partial and simultaneous influence between the buildings outside, building in the building, sanitation facilities and hygiene management on environmental health condition, analyze the effect of Puskesmas environment condition to the satisfaction and number of patient visit at Pekanbaru Health Center. This study used survey methods conducted at all public health centers in Pekanbaru City from April to August 2017. The sample size was 20 Puskesmas and 400 patients visited the Puskesmas. The tools and materials used in this research are observation instruments and use checklists and questionnaire interview instruments (questionnaires). The partial simultaneous effect of outbuildings, in-building buildings, sanitation facilities and hygiene management on the health condition of the puskesmas was used multiple regression tests, with the result of correlation of the condition of outsides to 0.321 outbuildings, buildings in 0.834, sanitation facilities 0.876 and cleanliness management 0.640. The direction of positive relationships shows the greater the assessment of the four variables will increasingly make the score of environmental health assessments getting bigger as well. Influence of health condition of environment of puskesmas toward patient satisfaction using multiple linear regression test and the result is 0,669. This shows a strong influence between environment health variable of puskesmas and satisfaction of respondent who come to visit puskesmas. R Square 0,448 or coefficient of determination mean 44,8% satisfaction of respondent can be explained by environment health variable of puskesmas. The influence of health condition of puskesmas on the number of patient visit using simple linear regression test and the result is 0,628. This shows a strong correlation between environment health variables of puskesmas with respondent visit coming to visit puskesmas. R Square 0,394 or coefficient of determination mean 39,4% of respondent visit can be explained by environment health variable of puskesmas while the rest is explained by other cause. It is necessary to increase health promotion and education about the importance of environmental health of puskesmas for the community about the health condition of the environment that fulfill the health requirement and increasing the role of Dinas Kesehatan in supervision of health of puskesmas environment to be better and become the reference of accreditation of puskesmas according to standard from the Ministry of Health RI.